2008
DOI: 10.3171/jns.2008.109.12.1012
|View full text |Cite
|
Sign up to set email alerts
|

Clipping of very large or giant unruptured intracranial aneurysms in the anterior circulation: an outcome study

Abstract: The treatment of very large or giant unruptured intracranial aneurysms is hazardous and complex and thus best performed only at major cerebrovascular centers with an experienced team of neurosurgeons, interventional neuroradiologists, neurologists, and neuroanesthesiologists. Surgery, with acceptable risks and excellent occlusion rates, is typically the treatment of choice in patients younger than 50 years of age. In older patients, the benefits of endovascular treatment versus surgery versus no treatment must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 22 publications
3
32
0
1
Order By: Relevance
“…They also mentioned that these age ranges typically present with a baseline disability and more comorbidities (p <0.05) associated with dependence than the younger age group. 17 Our results also showed that poor neurological grade had significant association with outcome following surgical obliteration of giant aneurysms. The result of the uni-and multivariate analysis showed the association between the H&H grade and GOS (p <0.001).…”
Section: Poor Neurological Gradesupporting
confidence: 63%
See 2 more Smart Citations
“…They also mentioned that these age ranges typically present with a baseline disability and more comorbidities (p <0.05) associated with dependence than the younger age group. 17 Our results also showed that poor neurological grade had significant association with outcome following surgical obliteration of giant aneurysms. The result of the uni-and multivariate analysis showed the association between the H&H grade and GOS (p <0.001).…”
Section: Poor Neurological Gradesupporting
confidence: 63%
“…25 mm, and occurrence of either an ischemic or hemorrhagic stroke. 17 In Orz et al's study on 310 patients with unruptured aneurysms, aneurysm size Figure 1 Bar chart depicting the distribution of Glasgow Outcome Scale score of the patients with giant aneurysms in anteriorly located lesions. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in that respect, most recent publications consist of endovascular series, and site-specific series comparing coiling versus clipping for cerebral aneurysms. 2,4,5,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]27,31,32, While these comparisons between competing techniques are obviously expected to occur, we feel that, as endovascular treatment for aneurysms continues to evolve and find its definite place in the therapeutic armamentarium, its proven benefits are best weighed in a multidisciplinary, complementary approach. We have experienced the benefits of this therapeutic philosophy as the natural evolution of a collaborative approach to these complex lesions from all possible therapeutic approaches to improve our patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Als Konsequenz besteht ein anhaltendes Risiko für eine Ruptur, weitere Behandlungen können erforderlich werden [4]. In etwa 3-9% kann es zu einem Verschluss oder einer relevanten Einengung benachbarter Gefäße mit der Gefahr eines Hirninfarkts und bleibenden neurologischen Defiziten kommen [2,8].…”
Section: -73% Aller Mikrochirurgisch Versorgterunclassified